Sistem Monitoring Air Qualty (Si Montoq) Menggunakan Sensor Mics-6814 dan DHT-11 Berbasis Internet of Things - Hifsan fauzian; Rahmat Hidayat (Sultan Publisher, 2024)
Along with the development of the era, technology is increasingly advanced and the use of fossil fuel vehicles is starting to be widely used and also more and more human populations are added to factories everywhere causing air quality to decrease and temperatures to warm up. Air pollution cannot be avoided. Air pollution is a condition in which the quality of the air decreases and is contaminated by substances, both harmless and harmful to human health. Some harmful gases in the air such as : CO, CO2, O3 and others. Carbon dioxide gas (CO2) Carbon dioxide is a gas that is colorless and odorless. When inhaled at concentrations higher than the concentration of carbon dioxide in the atmosphere, humans and other living things therefore cannot know if these gases are around. Humans can tell when they feel the impact. In this case, an air quality measurement tool has been created that can be carried anywhere easily and real-time measurements are used to measure air quality based on the Air Pollution Standard Index (ISPU). Using Sensor Mics-6814 to measure carbon dioxide gas (CO2) and DHT 11 to measure temperature.